Adsorption Capacity of Magnetic Activated Carbon Derived from Snake Fruit (Salacca zalacca) Seeds to Cd(II): Characteristics and Isotherm Model - Kusdarini, Esthi; Budianto, Agus; Kusuma, Maritha Nilam; Atiyatussa'adah, Eva (Reaktor, 2025)
Salak seeds are an agricultural waste that has the potential to be converted into magnetic activated carbon (MAC). The resulting MAC can be utilized for wastewater treatment, particularly in the adsorption of heavy metals. This study develops a method for producing MAC by forming activated carbon using a chemical activator without physical activation, chosen to reduce energy consumption. The activated carbon is then modified with Fe3O4 composite to render it magnetic and reusable. The objectives of this study are to 1) determine the optimal chemical activator concentration, 2) characterize magnetic activated carbon, 3) evaluate the adsorption capacity of MAC for Cd(II) in wastewater, 4) obtain an adsorption isotherm model of MAC for Cd(II) using the Langmuir and Freundlich models, and 5) analyze the surface morphology and elemental composition of MAC. Chemical activation was performed using an HCl-H3PO4 mixture with equal concentrations in a 1:1 volume ratio, with variable concentrations of 0.55, 1.05, 1.55, 2.05, and 2.55 M. MAC's characteristics and adsorption capacity were analyzed using proximate analysis, BET, SEM-EDX, and AAS. The results showed that: 1) the optimal HCl-H3PO4 concentration was 2.05 M, 2) MAC contained 1% moisture, 21.88% volatile matter, 38% ash, 39.13% fixed carbon, iodine number of 1218.24 mg/g, surface area of 175.604 m2/g, and an average pore volume of 26.8093 cc/g, 3) MAC adsorbed Cd(II) from wastewater with an efficiency of 80.12 – 87.75%, 4) the Langmuir isotherm model yielded R2 = 0.9847, qm = 35.0877 mg/g, and b = 0.0285 L/mg, whereas the Freundlich model yielded R2 = 0.9729, n = 1.5881, and kf = 7.6701 mg/g, and 5) MAC exhibited evenly distributed pores and contained dominant elements Fe (30.26%), C (29.08%), O (24.59%), Na (11.27%), with traces of Mg, Al, Mo, and Cl.